The Orientasi Amben Tengah pada Rumah Jawa di Desa Gedangan, Tulungagung - Rahima Dheta Yaistrina; Antariksa, Antariksa (EMARA: Indonesian Journal of Architecture, 2023)
The present study aims to examine the orientation and significance of Amben Tengah within traditional Javanese households, with a specific focus on the Tulungagung region in East Java. The exploration of Amben Tengah, a sacred space situated within these dwellings, is undertaken in the context of the house's overarching orientation and its association with cultural beliefs and practices. The findings of the study indicate that Amben Tengah generally corresponds to the alignment of the primary entrance of Javanese houses, which conventionally faces south, facilitating convenient entry from the main entrance. Nevertheless, there are differences in the orientation of Amben Tengah observed in buildings that no longer prioritise facing the mountain, so underscoring the significant role of Amben Tengah in the architectural design of Javanese houses. Notwithstanding alterations in its orientation, Amben Tengah persists in its role as a hallowed venue for religious practices, as well as for the provision of sleeping quarters and storage facilities. This study illuminates the lasting cultural importance of Amben Tengah in the architectural and spiritual context of traditional Javanese dwellings.